Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) (2x+1)^2+2(4x^2-2)+(2x-1)^2=4x2+4x+1+8x2-4+4x2-4x+1=16x2-2
Ta có : \(\frac{3\left(x^2+x-3\right)}{x^2+x-2}+\frac{x+3}{x+2}-\frac{x-2}{x-1}\)
\(=\frac{3\left(x^2+x-3\right)+\left(x+3\right)\left(x-1\right)-\left(x-2\right)\left(x-2\right)}{x^2+x-2}\)
\(=\frac{3x^2+3x-9+x^2+2x-3-x^2+4x-4}{x^2+x-2}\)
\(=\frac{3x^2+9x-16}{x^2+x-2}\)
`Answer:`
`a)`
`A=5(x+1)^2-3(x-3)^2-4(x^2-4)`
`=>A=5(x^2+2x+1)-3(x^2-6x+9)-4x^2+16`
`=>A=5x^2+10x+5-3x^2+18x-27-4x^2+16`
`=>A=(5x^2-3x^2-4x^2)+(10x+18x)+(5-27+16)`
`=>A=-2x^2+28x-6`
`b)`
`B=5(x+1)^2-3(x-3)^2-4(x+2)(x-2)`
`=2x(3x+5)-3(3x+5)-2x(x^2-4x+4)-[(2x)^2-3^2]`
`=6x^2+10x-9x-15-2x^3+8x^2-8x-4x^2+9`
`=(6x^2-4x^2+8x^2)-2x^3+(10x-9x-8x)+(-15+9)`
Thay `x=-7` vào ta được:
`B=10(-7)^2-2(-7)^3-7(-7)-6`
`=>B=10.49-2(-343)+49-6`
`=>B=490+686+49-6`
`=>B=1219`
\(=\left(x^2-3x+1+3-x-x\right)^2\)
\(=\left(-4x+4\right)^2\)
Ta có : (x+ 2)^2 - 2(x- 1) ( x+ 3) + x^2
= x^2 + 4x + 4 +( - 2x + 2)( x+ 3) + x^2
= x^2 + 4x + 4- 2x^2- 6x + 2x+ 6 + x^2
= 10
\(-2\left(x-2\right)\left(2+x\right)+\left(x-3\right)^2\)
\(=-2\left(x^2-4\right)+\left(x^2-6x+9\right)\)
\(=8-2x^2+x^2-6x+9\)
\(=-x^2-6x+17\)